Isolation and analysation of soybean agglutinin-specific binding proteins for erythrocyte membrane in different animal species. Issue 1 (1st January 2021) - Pan, Li; Yuan, Zhijie; Farouk, Mohammed Hamdy; Qin, Guixin; Bao, Nan
Abstract: Soybean agglutinin (SBA) represents the anti-nutritional molecule in soybean. This molecule agglutinates erythrocytes of several animal species. The specific binding of SBA to glycoprotein of the cellular plasma membrane is necessary for SBA to exert its toxic action. The sensitivity of erythrocyte to SBA for various species is different, however, the pathway is unclear. We aimed to optimise the method of extracting erythrocyte membrane (EM) and to analyse the pathway of the different sensitivity of erythrocyte to SBA in three animals species (rabbit as a rodent, pig as an omnivore, and bovine as a ruminant). The method of low osmotic haemolysis was used to extract the EM. To precipitate the EM, we evaluated the purification effects of three lysis bufferes, including NP-40, RIPA (medium) and RIPA (weak). All SBA-specific binding proteins (SSBP) on erythrocyte membranes were conducted using co-immunoprecipitation (CO-IP) and analysed using liquid chromatography coupled to tandem mass spectrometry (LC-MS-MS (Q-E)). The results showed that NP-40 lysis buffer was the most effective than the other two kinds of lysates to extract EM proteins. Functionally, the SSBP of EM could be divided into three categories in each animal, including cytoskeleton proteins, catalytic enzyme proteins and the functional regulatory proteins. The cytoskeleton proteins were the main different expressed proteins among the EM proteins in pig, rabbit than that in bovine, which may be one important reason for the difference of the SBA sensitivity. This research provides basis to reveal the pathway of SBA-induced hemagglutination differences in erythrocytes in different animal species. Highlights: We optimised the method of extracting EM to isolate and identify SSBP in different animal species. NP-40 lysis buffer was the most effective than the other two kinds of lysates to extract EM proteins. Cytoskeleton proteins were the main different expressed proteins among the EM proteins in pig, rabbit, and cow.